2012
DOI: 10.1097/mao.0b013e318268d50a
|View full text |Cite
|
Sign up to set email alerts
|

Particle Repositioning Maneuver Versus Brandt-Daroff Exercise for Treatment of Unilateral Idiopathic BPPV of the Posterior Semicircular Canal

Abstract: PRM is more effective treatment and as safe as B-D exercise in the short term for unilateral and idiopathic PC-BPPV, and although it does not reduce the probability of recurrence in the 4-year follow-up period compared with B-D exercise, it may delay the second recurrence's onset in those patients who had already experienced a single recurrence. Our study supports the use of PRM as the treatment of choice in unilateral and idiopathic PC-BPPV, although exercise may be also considered as an alternative treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 22 publications
2
53
2
1
Order By: Relevance
“…Long-term recurrence of BPPV is common, and the recurrence rate varies with time from 16 to 36% [22, 23]. So far, reports concerning recurrence by using the computer-controlled repositioning procedure are rare, as shown in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term recurrence of BPPV is common, and the recurrence rate varies with time from 16 to 36% [22, 23]. So far, reports concerning recurrence by using the computer-controlled repositioning procedure are rare, as shown in Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the majority of patients are adequately treated with 1 or 2 CRPs (79.4%-92.7%). 175,[258][259][260] However, 12.8% to 15.3% of patients will require a second CRP, and 5.1% will be classified as treatment failures after 2 CRPs. 175,[258][259][260] If initial therapy fails, the patient should be reassessed for BPPV diagnosis accuracy.…”
Section: Action Statement Profile For Statement 7amentioning
confidence: 99%
“…217 Concluding statements from the Cochrane review support intuitive thought that the primary intervention for patients with BPPV should be maneuvers (CRP) that directly treat the condition (eg, mechanical repositioning) but that other aspects of movement/habituation-based VR may further aide and support long-term functional recovery. 174,217 Although there is evidence that movement/habituation VR should not be considered as a substitute for CRP in the initial treatment of BPPV, there is a role for VR as adjuvant therapy in the management of selected patients with BPPV. BPPV can result in significant residual complaints of more generalized dizziness (abnormal motion sensitivities not associated with provocation of nystagmus) and definable abnormal postural control with heightened fall risk even after CRP has successfully resolved paroxysmal positional nystagmus.…”
Section: Action Statement Profile For Statement 4cmentioning
confidence: 99%
“…Brandt-Daroff egzersizleri olarak bilinen bu habitüasyon yönteminde amaç vertigoyu indükleyen hareketleri iki hafta boyunca günde 3 kez tekrarlayarak kişiyi bu duruma alıştırmaktır (20,21). Brandt-Daroff egzersizlerinin vertigoyu azalttığı fakat bir komplikasyon olan multikanal BPPV'ye neden olabileceği bildirilmektedir.…”
Section: -Benign Paroksismal Pozisyonel Vertigo Rehabilitasyonuunclassified